Revising Porter's five forces model for application in the travel and tourism industry - Andriotis, Konstantinos (My University, 2004)
This paper takes a new look at Porter’s five competitive forces model. In doing so, this work proposes a new competitive forces model centered on the travel and tourism industry that includes two additional forces, namely information technologies and government regulations, and adds an additional element to the buyers’ perspective, namely the power of intermediaries. This model is applied in the case of Greece and, although several limitations, from the findings it is proven as capable of explaining the competitive forces that affect the level of competition in the Greek travel and tourism industry.
Keywords: Porter’s competitive forces; Information technology; Intermediaries; Government regulation; Greece; Travel and tourism